Melchizedek, King of Sodom: how scribes invented the biblical priest-king - Cargill, Robert R. (Oxford scholarship online, 2019)
The biblical figure Melchizedek appears just twice in the Hebrew Bible, and once more in the Christian New Testament. Cited as both the king of Shalem - understood by most scholars to be Jerusalem - and as an eternal priest without ancestry, Melchizedek's appearances become textual justification for the establishment of the kingship of David in Jerusalem and the Christian priesthood. But what if the text was manipulated? Robert R. Cargill explores the Hebrew and Greek texts concerning, Melchizedek's encounter with Abraham in Genesis as a basis to unravel the biblical mystery of this character's origins.